Managing Recurrent Orbital Lymphangioma in a Pubertal Female with Negative Pressure Aspiration and Intralesional Bleomycin Injection: A Case Report - Chaudhary, Santosh; Pant, Aashish Raj; Badhu, Badri Prasad (Nepalese Journal of Ophthalmology, 2021)
Introduction: Management of orbital lymphangioma is challenging. Complete surgical excision is often impossible due to its infiltrative nature. Sclerosing agents have been used in its management with variable outcomes. We report a case of recurrent orbital lymphangioma managed with intralesional bleomycin. Case: A 14-year-old female presented with proptosis of the right eye for two weeks. She had a similar history at five years of age for which she underwent surgical excision. We performed negative pressure aspiration using a 20-gauge angiocatheter, injected bleomycin, and left the cannula in situ for repeat aspiration to maintain cyst collapse. Observation: The lymphangioma regressed, and there was no recurrence at six months of follow-up. Conclusion: This report highlights the use of negative pressure aspiration and intralesional bleomycin injection by minimal intervention using angiocatheter in the successful management of orbital lymphangioma.